Hepatectomy Followed by mFOLFOX6 Versus Hepatectomy Alone for Liver-Only Metastatic Colorectal Cancer (JCOG0603): A Phase II or III Randomized Controlled Trial. Issue 34 (1st December 2021) - Kanemitsu, Yukihide; Shimizu, Yasuhiro; Mizusawa, Junki; Inaba, Yoshitaka; Hamaguchi, Tetsuya; Shida, Dai; Ohue, Masayuki; Komori, Koji; Shiomi, Akio; Shiozawa, Manabu; Watanabe, Jun; Suto, Takeshi; et al.
Abstract : PURPOSE: Adjuvant chemotherapy after hepatectomy is controversial in liver-only metastatic colorectal cancer (CRC). We conducted a randomized controlled trial to examine if adjuvant modified infusional fluorouracil, leucovorin, and oxaliplatin (mFOLFOX6) is superior to hepatectomy alone for liver-only metastasis from CRC. PATIENTS AND METHODS: In this phase II or III trial (JCOG0603), patients age 20-75 years with confirmed CRC and an unlimited number of liver metastatic lesions were randomly assigned to hepatectomy alone or 12 courses of adjuvant mFOLFOX6 after hepatectomy. The primary end point of phase III was disease-free survival (DFS) in intention-to-treat analysis. RESULTS: Between March 2007 and January 2019, 300 patients were randomly assigned to hepatectomy alone (149 patients) or hepatectomy followed by chemotherapy (151 patients). At the third interim analysis of phase III with median follow-up of 53.6 months, the trial was terminated early according to the protocol because DFS was significantly longer in patients treated with hepatectomy followed by chemotherapy. With median follow-up of 59.2 months, the updated 5-year DFS was 38.7% (95% CI, 30.4 to 46.8) for hepatectomy alone compared with 49.8% (95% CI, 41.0 to 58.0) for chemotherapy (hazard ratio, 0.67; 95% CI, 0.50 to 0.92; one-sided P = .006). However, the updated 5-year overall survival (OS) was 83.1% (95% CI, 74.9 to 88.9) with hepatectomy alone and 71.2% (95% CI, 61.7 to 78.8) with hepatectomy followed by chemotherapy. In the chemotherapy arm, the most common grade 3 or higher severe adverse event was neutropenia (50% of patients), followed by sensory neuropathy (10%) and allergic reaction (4%). One patient died of unknown cause after three courses of mFOLFOX6 administration. CONCLUSION: DFS did not correlate with OS for liver-only metastatic CRC. Adjuvant chemotherapy with mFOLFOX6 improves DFS among patients treated with hepatectomy for CRC liver metastasis. It remains unclear whether chemotherapy improves OS. Abstract :